PERCEPÇÃO DOS ATORES ENVOLVIDOS NO PROJETO GARABI-ITA SOB O OLHAR DA EDUCAÇÃO AMBIENTAL - Lutz, Edela (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
The goal of this research was to investigate, under the point of view of environmental education,the perception of the actors involved in the Garabi-Itá project about the project and theparticipation of Escola Municipal de Ensino Fundamental Bom Pastor, and check the results of therecomposition of the riparian areas of arroio do Moinho. It was made a field research withobservation of tree-planting areas, held a visit and applied a questionnaire to owners, teachersand ex-monitors. Garabi-Itá project on properties in which the school helped in planting, wasconsidered positive by all actors involved in the search. Among the factors more noticeable by theowners, are less soil erosion, greater presence of birds, insects, reptiles and small mammals. Allfound satisfactory the participation of monitors in the project, and highlighted the importance ofthe role of school as motivating deployment projects in the community. It is relevant to the factmany ex-monitors have been motivated to participate in the project by colleagues, which showsthe importance of training of leaders within the school, as motivators of environmental education activities. It was evident the understanding that there should be a collective commitment tosolving the problems of arroio do Moinho, for the improvement of water quality and restorationof riparian forest. The research also showed that need some encouragement for participation inenvironmental projects, because 50% of producers, 75% of teachers and 60% of the ex-monitorsparticipate spontaneously, and the remainder only if it were invited, or obligation.